Sejarah dan Peran Habib Mundzir Al-Musawa dalam Dakwah Islam di Papua - Pratama, Fuad; Hasib, Kholili; Fasih, Ulum (Afkaruna: International Journal of Islamic Studies (AIJIS), 2024)
Islamic da'wah in Papua has high urgency considering that this region is one of the areas with a minority Muslim population in Indonesia. One of the figures who has an important role in Islamic propagation in Papua is Habib Mundzir Al-Musawa, he has made a significant contribution to the spread of Islamic values ​​in the Papua region, which is known for its cultural diversity. This research aims to examine the history of Habib Mundzir Al-Musawa's preaching in Papua, as well as analyzing his role in building the Muslim community in the region. Using a historical-qualitative approach, this research examines various written sources, interviews with local religious figures, and observations of the development of da'wah in Papua. The research results show that Habib Mundzir Al-Musawa plays an important role in building communication between religious communities, introducing peaceful Islamic teachings, and developing community-based preaching networks. Through lectures, knowledge assemblies and cultural approaches, he succeeded in bringing Islam closer to the Papuan people without eliminating local wisdom. Apart from that, his preaching also had an impact on the economic and social development of Muslims in Papua, especially in the aspects of education and welfare of the Muslim community. Thus, Habib Mundzir's role in preaching Islam in Papua does not only have a religious dimension but also a social and cultural one. This research provides new insight into inclusive da'wah strategies and the importance of a culturally based approach in spreading Islam in regions with high diversity such as Papua.